Uji Potensi Ekstrak Daun Kelor (Moringa oleifera) Sebagai Bahan Aktif Hand Sanitizer Alami - Thaal, Mario Bernardo; Pakan, Prisca Deviani; Woda, Rahel Rara (Cendana Medical Journal, 2023)
Abstract Background: Antiseptic hand sanitizers can prevent the transmission of infectious diseases. Antiseptic hand sanitizer consists of alcohol and synthetic chemicals which are relatively expensive. It is necessary to look for antiseptics from natural ingredients as active ingredients in hand sanitizers which are relatively cheaper, safe, effective and easily available to all levels of society. One of the plants cultivated as a medicinal plant is the Moringa oleifera. Objective: This research was conducted to determine the potential of Moringa oleifera leaf extract as an active ingredient in natural hand sanitizers. Methods : The type of research used is true experimental design with posttest only control group design. The treatment group in the study consisted of positive control for alcohol-based hand sanitizer, negative control for sterile aquadest, and a group of moringa oleifera leaf extract concentrations of 100%, 75%, 50%, 25%, 10%, 5%, 1% with 3 repetitions for each group against Staphylococcus aureus and Escherichia coli test bacteria. Data analysis used the One Way Anova statistical test with a confidence degree of 95%. Results : Based on the results of testing the antibacterial potential of Moringa oleifera leaf extract against the growth of Staphylococcus aureus and Escherichia coli showed that the extracts had antibacterial potential. One Way Anova test analysis showed that the value of p = 0.000 was smaller than α = 0.05 which means that there is a significant difference in the mean diameter of the inhibition zone between the treatment groups. Conclusions : Moringa oleifera leaf extracts have the potential as an active ingredient in natural hand sanitizers.